Motivation for Learning among Thai Students Studying Korean as a Foreign Language in Thailand - Song, Suji; Pornsima, Derek (Scholar: Human Sciences, 2017)
This study was conducted to examine the degree of motivation among Thai students learning Korean as a foreign language. The Attitude/Motivation Test Battery (AMTB), developed by Gardner (1985b), was used for measuring the degree of motivation. Two parts of the AMTB, integrative and instrumental goal orientation, were administered to 120 students at the King Sejong Institute Foundation’s Bangkok training institute during the 2014 academic year. The data collected were analyzed using a statistical software program. To analyze the data in accordance with the research objectives and hypothesis, different statistical methods such as mean and standard deviations, frequency were used. The study found a high degree of both integrative and instrumental motivation among the students.